Older peoples' experience of accessing emergency care - Considine, J.; Smith, R.; Hill, Keith; Weiland, T.; Gannon, J.; Behm, C.; Wellington, P.; McCarthy, S. (2010)
Background: Older ED users are more likely to be seriously ill, arrive by ambulance, spend more time in ED and require hospital admission. The aim of this study was to describe older people's experiences of accessing Emergency Department (ED) care. Methods: A descriptive approach was used. The study sites were three EDs in Victoria, Australia. Participants were ED patients aged 65 years or over and able to give informed consent. Observation of participants and care-givers and follow-up interviews were conducted from September to November 2008. Participant demographics were summarised using descriptive statistics and thematic analysis was used to analyse observation and interview data. Results: Results are based on data from 27 participant interviews and 12 care-giver interviews. Four major themes related to access to emergency care: (i) variation in ED use by older people, (ii) reluctance to access ED care, (iii) mixed experiences of waiting, and (iv) perceived factors influencing access to emergency care. Conclusions: Results of this study highlight important issues regarding access and triage elements of the ED experience for older people and their care-givers and should inform age appropriate triage and waiting processes to improve outcomes for older ED users. © 2010 College of Emergency Nursing Australasia Ltd.